Effects of moxonidine on sympathetic nervous system activity: An update on metabolism, cardio, and other target-organ protection - Eleni F Karlafti; Apostolos I Hatzitolios; Anastasios F Karlaftis; Maria S Baltatzi; Georgios G Koliakos; Christos G Savopoulos (Journal of Pharmacy and Bioallied Sciences, 2013)
Moxonidine is the newest, second-generation, centrally acting antihypertensive agent. It has selective agonist activity at imidazoline I1 receptors and less adverse effects than the other centrally acting drugs. This fact authorizes the frequent use of moxonidine in clinical practice, as monotherapy or in combination with other antihypertensive agents. Also, moxonidine has beneficial effects in obese and metabolic syndrome and in target-organs, such as heart and kidneys.